2020
DOI: 10.31926/but.ens.2019.12.61.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Banana Flower Nectar - Mediated Synthesis of Silver Nanoparticles

Abstract: Worldwide, the banana is the most famous fruit on the market. All parts of the plant have been used over the years in medicine and the curative properties of the banana are well known. No reports about the study of the nectar of banana flowers could be find, except those on extracts from different parts of the plant, this being the reason of starting synthesis of silver nanoparticles (AgNPs) from the banana flower's nectar. Because conventional methods for producing NPs are expensive, toxic and nonorganic in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Notably, the latex samples come from a natural source inferring a natural type of resin and it is comparable with the absorption bands of terpenoid resin. The spectra of terpenoid resin [36] in Table 2 served as a reference which showed that Artocarpus species latex share common peaks such as 2930-2958 cm -1 C-H stretches, 1725-1750 cm -1 esters [37], 1695-1715 cm -1 carbonyl bands, 1448-1467 cm -1 aromatic ring stretch, 1382-1387 cm -1 C-H bending of methyl and Methylene groups, 1028-1038 cm -1 Acid resins, and 887-897 cm -1 C-C vibrations [37,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the latex samples come from a natural source inferring a natural type of resin and it is comparable with the absorption bands of terpenoid resin. The spectra of terpenoid resin [36] in Table 2 served as a reference which showed that Artocarpus species latex share common peaks such as 2930-2958 cm -1 C-H stretches, 1725-1750 cm -1 esters [37], 1695-1715 cm -1 carbonyl bands, 1448-1467 cm -1 aromatic ring stretch, 1382-1387 cm -1 C-H bending of methyl and Methylene groups, 1028-1038 cm -1 Acid resins, and 887-897 cm -1 C-C vibrations [37,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the FTIR spectra of banana blossom peels adsorbent. The existence of significant hydroxyl (O-H) stretching vibration of cellulose molecules is related to the broad peak that appeared in the region of 3500 cm À1 to 3300 cm À1 [21][22][23][24]. Next, peak at 2920 cm À1 is characteristic of C-H stretching.…”
Section: Structural Characteristicmentioning
confidence: 99%
“…These phytochemicals possess diverse phytochemical properties such as antioxidation, antibacterial, anticancer, antidiabetic, and anti-inflammatory action (Jamuna and Nandini, 2014;Sitthiya et al, 2018). Experiments have shown that the polyphenolic compounds present in banana flowers could act as both reducing and capping agents for the synthesis of AgNPs (Stirbescu et al, 2019). The preparation of AgNPs from banana flower extract can not only reduce the preparation cost, but also maximise the utilisation of agricultural resources.…”
Section: Introductionmentioning
confidence: 99%